2017
DOI: 10.1177/0308022617709165
|View full text |Cite
|
Sign up to set email alerts
|

Occupations outside the home: Experiences of people with acquired brain injury

Abstract: Introduction: Understanding those occupations outside the home that people with acquired brain injury find difficult, including the influencing factors, may help to develop appropriate support. The aim of this paper was to explore and describe how people with acquired brain injury experience engagement in occupations outside the home. Method: This qualitative study included repeated semi-structured interviews with eight working-age persons with acquired brain injury, which were analysed by a constant compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In this way, ICT could assist the creation of a person-centred care relationship. However, the use of ICT in rehabilitation has to be based on the needs and ability of patients, recognizing that they might experience difficulties in handling ICT tools due to their impairments and activity limitations [15][16][17]31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, ICT could assist the creation of a person-centred care relationship. However, the use of ICT in rehabilitation has to be based on the needs and ability of patients, recognizing that they might experience difficulties in handling ICT tools due to their impairments and activity limitations [15][16][17]31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the technology might be perceived as being difficult to handle for people with acquired brain injury, including stroke, due to cognitive deficits. Thus, it is important for professionals to note whether additional support is required [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Participation commonly include engagement in activities in numerous places. After a stroke, it can be challenging to be engaged in activities in places outside the home [1][2][3][4]. Recent research has found that people with a severe or moderate disability after a stroke visit fewer places, compared to those with good recovery after stroke [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the possibilities for participation are influenced by transportation to and from different places where the activities take place [3,10,11]. When the place of residence is located in areas where access to public transportation is limited, a car is particularly important for transportation.…”
Section: Introductionmentioning
confidence: 99%
“…A stroke may impact a person on many different levels, and returning to life as it was before stroke can be a long-term struggle (1). For many years after stroke, the physical, cognitive and emotional conse-quences can have a substantial impact on a person's participation in everyday life at home and in society (2)(3)(4)(5). The client-centred approach is highlighted in occupational therapy models (6,7) and recommended for rehabilitation after stroke in order to achieve a successful rehabilitation outcome.…”
mentioning
confidence: 99%